STRATEGI PT PERTAMINA E&P ASET 5 STRUKTUR KLAMONO DALAM MENERAPKAN KEBIJAKAN CORPORATE SOCIAL RESPONSIBILITY - Prayudi Prayudi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat UPN Veteran Yogyakarta, 2015)
This study analyzes how corporate social responsibilities (CSR) run in the company. Inparticular, this research looks at CSR strategy of PT Pertaminna E&P Asset 5 Klamonogljycture. CSR is the continuing commitment o) compames Vo V e t e Mcontribute to economic development whilst improving tie quality of Ilk Of tllfienvironment and their families as well as local communities and society in general. tJsjugqualitative research method, the research reveals the fact that the company I analyzed hadadopted CSR into its business strategic pohcy. It focused on five aspects: health, economic,social, education, and infrastructure.Keywords : corporate social responsibility, investasi sosial